2008
DOI: 10.1590/s1516-35982008000700014
|View full text |Cite
|
Sign up to set email alerts
|

Digestibilidade do fósforo de alimentos de origem vegetal determinada em suínos em crescimento e terminação

Abstract: RESUMO -Objetivou-se determinar os coeficientes de digestibilidade aparente (CDAP) e verdadeira (CDVP) do fósforo de 11 alimentos de origem vegetal utilizados na alimentação de suínos. Foram utilizados 78 animais mestiços distribuídos em um delineamento experimental inteiramente casualizado, em arranjo fatorial 2 × 2 × 13 (metodologia × fase × tratamento) e três repetições por tratamento (alimento-teste). Os coeficientes de digestibilidade foram avaliados utilizando-se, simultaneamente, duas metodologias (cole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
2
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 10 publications
0
9
2
8
Order By: Relevance
“…The amount phosphorus excreted in the feces was found to decrease between the powder and microgranular phosphate treatments (P<0.05), with the lowest excretion occurring when the phosphate was in microgranular form. The phosphorus excreted in the urine was not affected (P>0.05) by the supplemental P sources, which is in disagreement with the data presented by Teixeira et al (2004) and Bünzen (2009), who observed that the P content in the feces and urine increased with the level of P in the diet. The estimated endogenous P values were similar (P>0.05) among the treatments.…”
contrasting
confidence: 93%
See 1 more Smart Citation
“…The amount phosphorus excreted in the feces was found to decrease between the powder and microgranular phosphate treatments (P<0.05), with the lowest excretion occurring when the phosphate was in microgranular form. The phosphorus excreted in the urine was not affected (P>0.05) by the supplemental P sources, which is in disagreement with the data presented by Teixeira et al (2004) and Bünzen (2009), who observed that the P content in the feces and urine increased with the level of P in the diet. The estimated endogenous P values were similar (P>0.05) among the treatments.…”
contrasting
confidence: 93%
“…These values were lower than the 28 and 56mg/(kg P 0.75 × day) obtained by Fan et al (2001) and Ajakaiye et al (2003) with 14-and 49-kg animals, respectively. This value oscillates among the observed values of 139, 174, 232, 258 and 310mg P/kg DM intake by animals fed diets without P (PETERSEN & STEIN, 2006;BAKER, 2011;TEIXEIRA et al, 2004;BÜNZEN, 2009;FAN et al, 2001). The retained P was lower (P<0.05) in the animals that consumed CTR compared with other treatments.…”
mentioning
confidence: 61%
“…Coeficientes de digestibilidade de matéria seca (CDMS), energia bruta (CDEB), proteína bruta (CDPB), cálcio (CDCa), fósforo (CDP), fibra bruta (CDFB), energia digestível (ED), energia metabolizável (EM), e proteína, cálcio, fósforo e fibra digestíveis de farinheta, farelo fino, farelo grosso, farelo de trigo e farelo grosso moído para suínos em crescimento (1) . mas não no balanço, justifica as diferenças observadas (Bünzen et al, 2008), que foram acima de 13% entre as duas metodologias. A digestibilidade aparente de MS, EB e PB da farinheta foi significativamente maior que a dos demais alimentos avaliados (Tabela 4).…”
Section: Variávelunclassified
“…Several methods have been used to measure endogenous losses of P in pigs (Fernández, 1995; Fan et al, 2001; Petersen and Stein, 2006; Bünzen et al, 2008). Endogenous losses of Ca in cattle (Visek et al, 1953; Hansard et al, 1957; Martz et al, 1999) and in chickens (Cowieson et al, 2004; Liu et al, 2012) have been reported.…”
Section: Digestibility Of Calciummentioning
confidence: 99%